Fotoenvelhecimento acelerado do microplástico poli (tereftalato de etileno): propriedades físicas, químicas, morfológicas e adsorção de pesticida - Costa, Thaís Bessa de Oliveira (2024)
Microplastics (MP) in the environment are a constant concern, as these plastic particles can have a series of negative impacts on environments, especially aquatic environments. Due to entanglement and ingestion by marine animals, microplastics can lead to the death of aquatic animals, which interferes with aquatic life and, consequently, the life of human beings. In addition to the direct mortality of animals, microplastics can be dispersed in the environment and have great potential for transporting organic and inorganic contaminants up trophic chains, due to their adsorptive capacity. With this in mind, the main aim of this study was to investigate the effect of photoaging polyethylene terephthalate (PET) microplastics on their physical, chemical and morphological properties, using accelerated aging chambers with UV-B lamps, and to correlate this with the ability of these materials to adsorb the pesticide chlorpyrifos. Samples of PET microplastic were photo-aged in a chamber containing UV-B lamps for different exposure times (1h, 4h, 6h and 8h). The morphological, chemical and structural characteristics of the materials obtained after photodegradation were monitored and compared with natural PET using Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), Energy Dispersive X-Ray Spectrometry (EDS), Fourier Transform Infrared Spectroscopy (FTIR), Zero Charge Potential (pHPCZ) and Thermogravimetry (TG). The Percentage of Crystallinity (using XRD data) and Carbonyl Index (CI) (using FTIR data) were also calculated. SEM analyses revealed an increase in roughness and the appearance of pores in the PETs aged at 6 and 8 hours, which proves that the materials showed morphological changes after the photoaging process. It was not possible to observe a statistically significant reduction in the percentage of crystallinity of the photodegraded PETs when compared to natural PET, however, the infrared analysis (FTIR) revealed bands close to the 1720 cm-1 wave number, which corresponds to the carbonyl groups (C=O), which were more intense for the photo-aged materials, indicating that the materials suffered oxidation after UV-B irradiation. From the calculation of the Carbonyl Index, it was possible to observe an increase in the CI directly linked to increased exposure to UV-B radiation. Thermogravimetry showed that natural PET and PET- 1h had similar thermograms with only one degradation stage and the other PETs aged for 4h, 6h and 8h showed a second degradation peak, but with a lower intensity, indicating that there was no significant change in the thermal stability of the materials after the photo-aging process. The pHPCZ values decreased after photodegradation, probably due to the increase in oxygencontaining groups resulting from UV-B photo-oxidation. The adsorption analyses revealed a statistically significant increase in adsorption capacity for all aged PETs when compared to natural PET, with adsorption capacities of 1.31; 1.48; 1.58; 1.51 and 1.56 mg/g for PET, PET- 1h, PET-4h, PET-6h and PET-8h, respectively. Due to the increase in interaction area (increase in roughness and cavity), hydrophobic and π-π interactions between photodegraded PET and chlorpyrifos were favoured. Based on the data obtained, it is considered that PET in the environment has its physical, chemical and morphological properties altered after exposure to UV-B radiation.